Coal mining wastes valorization as raw geomaterials in construction: A review with new perspectives. (15th February 2022) - Vo, Thanh Liem; Nash, William; Del Galdo, Marco; Rezania, Mohammad; Crane, Rich; Mousavi Nezhad, Mohaddeseh; Ferrara, Liberato
Abstract: Historically coal mining wastes have been viewed as heterogenous and hazard-prone geomaterials. Given that failures of colliery tips and tailing dams are reported on a regular basis, reclamation of coal mining wastes from storage facilities is increasingly being considered. There is a resistance to the use of coal mining waste in construction industry despite scattered but growing reports of successful applications. As the construction industry around the globe seeks to reduce its carbon emissions by looking for supplements for cement, the voluminous amount of coal mining wastes currently stored in spoil heaps and impoundment facilities present a potential source of raw materials. This article reviews the literature on the geochemical, geotechnical and structural engineering properties of coal mining waste geomaterials to assess their suitability as replacement for both aggregates and binders in concrete and cementitious composites (as opposed to reviewing the properties of those products themselves). It is found that coal mining wastes are indeed good candidates (as raw materials) for the uptake and process into higher level construction purposes. Geochemically, the key to a successful upcycling operation is the knowledge of their mineral contents (which is typically diverse and varies from one mine to another) and the processes they undergo while being transformed into constituents of new materials. The few studies on concretes made with coal mining wastes indicate that the mineralogical and mechanical characterization of the wastes to obtain a mix featuring strength and durability performance that meets specification is important to a successful utilization. In the geotechnical literature, coal mining wastes are known to be highly heterogeneous and may host expandable minerals with potential durability problems. However, this review also found that simple geotechnical index tests can be conducted to yield useful information for the initial screening of coal mining wastes into a construction product. The state-dependent properties of coal mining wastes (e.g., water retention, hydraulic conductivity, shear strength) are found to be governed by complex factors such as coal content, particle size and shape, pore size and shape, and the presence and interaction of pore air and pore water in the void space, some of these are well-studied but much of these are to be further researched.